2011
DOI: 10.1111/j.1440-1630.2011.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Driving to Learn in a powered wheelchair: Inter-rater reliability of a tool for assessment of joystick-use

Abstract: When comparing the three raters' assessments with that of LN (N = 72), the calculation gave a weighted kappa value of 0.85. All raters judged the tool as having a high degree of usability for assessing phases of joystick-use. Minimal differences were found between the experienced and inexperienced raters. CONCLUSION AND SIGNIFICANCE OF THE STUDY: The inter-rater reliability of the assessment tool was very good. The findings indicate that the tool is reliable and has clinical usability in occupational therapy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 18 publications
(41 reference statements)
2
24
0
Order By: Relevance
“…The assessment of actual phase guided facilitators' choice of individually appropriate facilitating strategies. The assessment tool was developed and tested in clinical practice, and a test for interrater reliability resulted in a weighted k of .85 (Nilsson, 2007;Nilsson, Eklund, & Nyberg, 2011).…”
Section: Identification Of Phases In Learning Tool Usementioning
confidence: 99%
“…The assessment of actual phase guided facilitators' choice of individually appropriate facilitating strategies. The assessment tool was developed and tested in clinical practice, and a test for interrater reliability resulted in a weighted k of .85 (Nilsson, 2007;Nilsson, Eklund, & Nyberg, 2011).…”
Section: Identification Of Phases In Learning Tool Usementioning
confidence: 99%
“…The ALP tool is an assessment tool that originated from two separate GT studies, both focused on discovering the process of learning powered mobility [1,[11][12][13][14][15][16][17][18]. The ALP tool is grounded in extensive data taken from a number of sources including a wide group of participants over an extensive period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Focus for using the ALP tool is to understand where the learner is in the process and provide appropriate facilitation in addition to recognizing changes and achievements. The interrater reliability study of Nilsson et al's previous eight-phase assessment tool [18] showed a very good weighted kappa value (0.85), and that tool also showed responsiveness to change when it was used to assess the outcome of her 45 powered wheelchair learners with profound cognitive disabilities [1]. A study of the intra-and interrater reliability of the ALP instrument, as well as of its responsiveness to change, would strengthen the scientific evidence of its use in clinical practice.…”
Section: Trustworthiness Of Alp Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Tefft et al, Furumasu et al published the pediatric powered wheelchair skills test, which used a five-point scale to quantify a child's driving ability [47]. In 2011, Nilsson et al reported several strategies that have been applied to teach EPW driving skills for children with cognitive disabilities [48, 49]. These studies have demonstrated the strong association of cognitive, sensory, and motor assessments with better training strategies in children [48].…”
Section: Introductionmentioning
confidence: 99%